Handling the problems and opportunities posed by multiple on-chip memory controllers - Awasthi, Manu; Nellans, David; Sudan, Kshitij; Balasubramonian, Rajeev; Davis, Al (PACT '10 : proceedings of the Nineteenth International Conference on Parallel Architectures and Compilation Techniques : September 11-15, 2010, Vienna, Austria, 2010)
Modern processors such as Tilera's Tile64, Intel's Nehalem, and AMD's Opteron are migrating memory controllers (MCs) on-chip, while maintaining a large, at memory address space. This trend to utilize multiple MCs will likely continue and a core or socket will consequently need to route memory requests to the appropriate MC via an inter- or intra-socket interconnect fabric similar to AMD's HyperTransport™, or Intel's Quick-Path Interconnect™. Such systems are therefore subject to non-uniform memory access (NUMA) latencies because of the time spent traveling to remote MCs. Each MC will act as the gateway to a particular piece of the physical memory. Data placement will therefore become increasingly critical in minimizing memory access latencies. To date, no prior work has examined the effects of data placement among multiple MCs in such systems. Future chip-multiprocessors are likely to comprise multiple MCs and an even larger number of cores. This trend will increase the memory access latency variation in these systems. Proper allocation of workload data to the appropriate MC will be important in reducing the latency of memory service requests. The allocation strategy will need to be aware of queuing delays, on-chip latencies, and row-buffer hit-rates for each MC. In this paper, we propose dynamic mechanisms that take these factors into account when placing data in appropriate slices of the physical memory. We introduce adaptive first-touch page placement, and dynamic page-migration mechanisms to reduce DRAM access delays for multi-MC systems. These policies yield average performance improvements of 17% for adaptive first-touch page-placement, and 35% for a dynamic page-migration policy.